Correlational Study between Academic Performance, Co-Curricular Activities and Extracurricular Activities in a Select Educational Institution - Gutierrez, Ernell Bautista (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Academic performance is usually viewed in terms of numerical figures as manifested in the individual activities of students in the classroom. As mentioned by Husaini, Y & Shukor, N (2022), students' Academic Performance is vital for assessing a student's standing within a university. It makes it possible for academic staff, educational administrators, and decision-makers to precisely evaluate students taking various courses throughout a semester. Additionally, it served as a cautionary tale for the students to assess their performance level and make subsequent improvements Supported by the results from the study of Husaini, Y & Shukor, N (2023), students' academic performance is vital for assessing a student's standing within a university. It makes it possible for academic staff, educational administrators, and decision-makers to precisely evaluate students taking various courses throughout a semester. The study investigated the relationship between student’s academic performance and their participation on Co-curricular and Extra-curricular Activities. It further investigated if Age, Sex and Academic Program would cause significant differences in their Academic Performance, Co-curricular Activities and Extra-curricular Activities. A total of 75 students from the Business Administration program participates in the study. The students were from the four (4) academic majors namely; Marketing Management, Financial Management, Operation Management and Human Resource Management. Results revealed that Co-curricular Activities and Extra-curricular Activities of the students are both significantly related to their academic performance with P-value < 0.05. Likewise, the Age, Sex and Academic Program of the students did not cause any differences on their assessments towards Academic Performance, Co-curricular Activities and Extra-curricular Activities with P-value of >0.05.